Hubungan Postur Kerja Terhadap Keluhan Low Back Pain Pemetik Teh PT Perkebunan Tambi Wonosobo - Sumardiyono; Fajar, Hikmah Nurul; Mulyani, Sri (Sekolah Vokasi, Universitas Sebelas Maret, 2023)
Tea pickers are workers in the plantation sector who still do their work manually, with repetitive movement, and carry out the load in their back during labor, which can cause non-ergonomic work posture. This causes ergonomic complaints in workers, known as low back pain which is a complaint of back pain caused by several factors, including unnatural work posture, age, and years of service. The research was observational analytic with a cross-sectional design. The sampling technique in this research was total sampling with the total respondents of 36 tea pickers at PT Perkebunan Tambi Wonosobo, Block Bismo of UP Bedakah. This study used the RULA measurement method to measure work posture and the Oswestry Low Back Pain Disability Questionnaire to measure low back pain complaints. Data analysis techniques used the Somers'd correlation test to determine the correlation between work posture and low back pain Tea Pickers at PT Perkebunan Tambi Wonosobo. The results of the research on 36 respondents showed that there was a significant correlation between work posture and low back pain among tea pickers with a p-value = 0.014 (p<0.05) and a correlation coefficient (r) is 0.410 which is included in a moderate correlation with a positive correlation direction. The conclusion of this study there was a correlation between work posture and low back pain complaints of tea pickers at PT Perkebunan Tambi Wonosobo, Bismo Block of UP Bedakah.